2001
DOI: 10.1086/322528
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive Black Holes in Active Galactic Nuclei. I. The Consistency of Black Hole Masses in Quiescent and Active Galaxies

Abstract: We report the first results of a program to measure accurate stellar velocity dispersions in the bulges of the host galaxies of active galactic nuclei (AGNs) for which accurate black hole (BH) masses have been determined via reverberation mapping. We find good agreement between BH masses obtained from reverberation mapping, and from the M • − σ relation as defined by quiescent galaxies, indicating a common relationship between active and quiescent black holes and their larger-scale environments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
318
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(356 citation statements)
references
References 31 publications
(28 reference statements)
38
318
0
Order By: Relevance
“…Ferrarese and Merritt (2000) and Gebhardt et al (2000a) have found that MBH masses of inactive galaxies are better correlated with the stellar velocity dispersion in the bulge than with the bulge luminosity. Apparently this relation holds also for AGNs: the few Seyfert galaxies with stellar velocity data and reverberation BH mass estimates seem to be consistent with the BH-velocity dispersion relation of inactive galaxies (Gebhardt et al 2000b), a conclusion strengthened by observations of the velocity dispersion in reverberation mapped Seyfert galaxies (Ferrarese et al 2001). Seyfert 1 galaxies and quasars).…”
Section: Introductionsupporting
confidence: 54%
“…Ferrarese and Merritt (2000) and Gebhardt et al (2000a) have found that MBH masses of inactive galaxies are better correlated with the stellar velocity dispersion in the bulge than with the bulge luminosity. Apparently this relation holds also for AGNs: the few Seyfert galaxies with stellar velocity data and reverberation BH mass estimates seem to be consistent with the BH-velocity dispersion relation of inactive galaxies (Gebhardt et al 2000b), a conclusion strengthened by observations of the velocity dispersion in reverberation mapped Seyfert galaxies (Ferrarese et al 2001). Seyfert 1 galaxies and quasars).…”
Section: Introductionsupporting
confidence: 54%
“…One important application for such measurements is as a consistency check on the black hole masses determined from reverberation mapping of nearby Seyfert 1 galaxies (Wandel, Peterson, & Malkan 1999;Kaspi et al 2000). Gebhardt et al (2000b) and Ferrarese et al (2001) have shown that the reverberation masses of Seyfert 1 galaxies are in good agreement with the M −σ relation of nearby galaxies; this is a reassuring sign that the reverberation measurements give reasonable estimates of the black hole masses. Near-infrared spectra of two PG quasars, centered on the Ca II triplet spectral region.…”
Section: Can the Stellar Velocity Dispersions Of Quasar Host Galaxiesmentioning
confidence: 94%
“…Although large-scale bars can produce gas inflow (e.g., Combes & Gerin 1985;Sakamoto et al 1999) and in some cases also drive powerful starbursts (e.g., Knapen et al 2002;Jogee et al 2005), a correlation between large-scale bars and nuclear activity has not yet been verified (e.g., Mulchaey & Regan 1997). This lack of correlation is probably related to the different timescales for bar-induced gas inflow ( 300 Myr, Jogee et al 2005), AGN duty cycles (∼10 7 yr), and intermittent active accretion every ∼10 8 yr (Ferrarese et al 2001;Marecki et al 2003;Janiuk et al 2004;Hopkins & Hernquist 2006;King & Pringle 2007). The comparison of these different timescales suggests that most AGN are in an intermediate phase between active accretion episodes making the detection of galaxies with nuclear accretion somewhat difficult.…”
Section: Introductionmentioning
confidence: 99%